Sobolev cohomology for locally polycylindrical domains - Patrick W. Darko (International Journal of Mathematics and Mathematical Sciences)
The Cauchy-Riemann equation is solved with LP-Sobolev space estimates and the result is used to obtain vanishing theorems on locally polycylindrical domains.